Using L1 in Teaching Vocabulary to Low-Proficiency-Level Students in The University College of Khafji for Female Students - Aldhefeir, Abeer Hamed (Journal of Curriculum and Teaching Methodology, 2025)
This qualitative research investigates the effectiveness of using the learners’ first language (L1) in teaching vocabulary to low-proficiency English students at the College of Khafji, Saudi Arabia. Challenging the prevailing notion that vocabulary instruction should solely occur in English, the study explores the preferences of students regarding L1 usage in their learning process. Through qualitative open-ended questionnaires administered to twenty female students, findings indicate that L1 significantly enhances vocabulary comprehension, engagement, and confidence among learners. The use of clear definitions and contextual explanations in Arabic facilitated a deeper understanding of English vocabulary, leading to improved learning outcomes. This study contributes valuable insights to English language teaching methodologies, advocating for the integration of L1 in vocabulary instruction to better support low-proficiency learners and enhance their academic performance. The implications of these findings suggest a need to reconsider existing pedagogical approaches in vocabulary education within the Saudi context.